Tantangan Literasi Digital Bagi Orang Tua palam Mengelola Pengaruh Digital pada Anak Usia Dini - Rafika Hayati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The rapid development of digital technology has significantly influenced the lives of young children, affecting their cognitive, social, and emotional development. However, this advancement also presents challenges for parents in guiding their children to avoid the negative impacts of digital exposure. This article aims to explain the importance of digital literacy for parents, identify the main challenges they face in managing children’s technology use, and offer effective strategies for digital parenting. The method used is a literature review based on recent academic sources. The findings show that parents’ digital literacy plays a crucial role in shaping healthy digital behavior in early childhood. Parents with high levels of digital literacy can act as filters, facilitators, and role models in using technology wisely. Collaboration among families, educational institutions, and the government is also necessary to create a safe and supportive digital environment for children’s optimal development.